BARkod, barKOD or BARKOD? Bulgarian Speakers and their Production of Stress (Philologia, 2021)
The aim of this paper is to investigate the production of stress in 2-, 3-, 4-, and 5-syllable N+N constructions borrowed from English into Bulgarian by two groups of speakers. The first group consists of 20 Bulgarian learners of English, who are first-year university students in English and American Studies at Sofia University “St. Kliment Ohridski”. The second group consists of 20 Bulgarian speakers with no knowledge of English. I will try to determine what stress patterns Bulgarian learners of English produce in native and borrowed N+N constructions and will also explore whether their knowledge of English has any influence on their production. Then, I compare those results to the production of the speakers from the second group of respondents, who have no command of English. The experiment consists of two tests – a production, and a perception test (a judgement task).
Keywords: stress; borrowings; N N contructions; English; Bulgarian; production